Factores relacionados con la sexualidad en adolescentes varones – Tarapoto - Águila Arévalo, Diana Del (1995)
This descriptive transversal study was performed using the information in-situ; polling a total of 738 men teens covered in the 15 to 19 year-old age group; population that is took of them colleges side of district of Tarapoto with the purpose of knowing some aspects on health reproductive of our teenagers.